Comparison of empirical and predicted ultraviolet aircraft signatures - James, Itor; Richardson, Mark A.; O'Keefe, Eoin (SPIE - International Society for Optics and Photonics, 2019)
In light of the potential threat to aircraft from missiles using ultraviolet (UV) wavebands, it is important to understand the signature of an aircraft and how this can be predicted. This study compares empirical UV signature data to modeled data from camouflage electro-optical simulation (CAMEOSIM) to determine how well the contrast between the object and the background can be predicted using local knowledge of the atmosphere. CAMEOSIM uses the standard moderate resolution atmospheric transmission (MODTRAN) model to estimate the radiative transfer through the atmosphere. Both MODTRAN and CAMEOSIM are well validated in visible and infrared wavebands, and MODTRAN can accurately predict UV radiative transfer. Unfortunately, the work so far has concentrated on bulk transfer to describe the sky background in the UV where the aircraft scene is typically a negative contrast “hole” in a positive sky background. Importantly, path-to-path scattering is a key consideration in this scene since it is this that will tend to blur the edges of an object and reduce the contrast associated with it. A developed understanding of the limitations is required. It is determined that prediction is possible up to the ranges of 5 km. The local visibility (in km) is required for this prediction.
Keywords: ultraviolet; aircraft; signature; prediction; modelling; atmosphere